1978
DOI: 10.1042/bj1720301
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent Golgi-vesicle fusion and cathepsin B in the conversion of proalbumin into albumin in rat liver

Abstract: 1. An enzyme from rat liver that converts proalbumin into albumin is described. Partial purification, inhibitor studies and the conditions for maximum activity suggest that the enzyme is cathepsin B. 2. A membrane-bound enzyme, located mainly in lysosomes, also converts proalbumin into albumin. This appears to be a membrane-bound form of cathepsin B. 3. Isolated Golgi vesicles, incubated under conditions suitable for cathepsin B, convert endogenous proalbumin into albumin. 4. This conversion in Golgi vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…One of the roles of the lysosomes in secretory cells might be to degrade endogenous secretory products when the discharge of the products is depressed under certain physiological conditions (7,22). Ikehara et al (10) reported that proalbumin was converted to albumin in secretory vesicles of rat liver and almost the same results have reported by Quinn et al (19). Smith et al (23) suggested that acid protease included in immature secretory vesicles may also participate in the conversion of proinsulin to insulin in rat pacreas.…”
Section: Methodssupporting
confidence: 73%
“…One of the roles of the lysosomes in secretory cells might be to degrade endogenous secretory products when the discharge of the products is depressed under certain physiological conditions (7,22). Ikehara et al (10) reported that proalbumin was converted to albumin in secretory vesicles of rat liver and almost the same results have reported by Quinn et al (19). Smith et al (23) suggested that acid protease included in immature secretory vesicles may also participate in the conversion of proinsulin to insulin in rat pacreas.…”
Section: Methodssupporting
confidence: 73%
“…Chloroquine was reported to inhibit the cathepsin B activity in the crude homogenatc of fibroblasts [29]. Although cathepsin B was suggested to be a candidate for the processing enzyme for proalbumin [30], its involvement in the conversion of proinsulin and parathyroid hormone was not confirmed by the experiments using the purified cathepsin B [31, 321. In fact, addition of leupeptin (100 pgiml), a specific inhibitor of cathepsin B, exerted no inhibitory effect on the conversion of proalbumin in cultured hepatocytes (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…Golgi vesicle fractions were prepared as described by Quinn and Judah [16]; a critical difference, however, was that no EDTA was incorporated in the various sucrose density solutions. Briefly, livers were homogenized in ice-cold 0.25 M sucrose; nuclei, mitoehondria and cell debris were removed by centrifugation (9500 x gay, 15 min).…”
Section: Methodsmentioning
confidence: 99%